Mathieu Larnaudie's Les Effondres. Power, money, and fiction... - Maftei, Magda Mara (Romanica Olomucensia, 2020)
This paper analyses Mathieu Larnaudie's novel Les Effondres, which was published by Editions Actes Sud in 2010. Its aim is to show that his novel is built around two perspectives, literary and economic, but also to emphasize the belonging of Mathieu Larnaudie to the Inculte collective. This membership assures him a unique place. The Incultes are implementing a new way of looking at the real: it is the multifaceted nature of the interpretation of the real that interests them. As Les Effondres illustrates perfectly, it is about a kind of de-totalization practised by the novel since the author leaves to the reader the possibility of reconstructing the text in his own way. The Incultes no longer have ideological force. Larnaudie's novel is not a personalized denunciation, much less a chronicle of the economic crisis that began in 2007, but a treatment of information already known by all his contemporaries, in a manner that is specific for a writer belonging to the Inculte collective. The analysis of Larnaudie's text shows us the very good knowledge the writer has of the economic problems caused by the subprime crisis and it confirms his strong membership of the Inculte collective. Consequently, it can once again be concluded that a literary work is indeed the product of a socio-economic, political, and cultural context, belonging to which plays a determining role in the constitution of a work.
Keywords: Mathieu Larnaudie; Les Effondres; subprime crisis; the Inculte collective; power; money